2020
DOI: 10.1029/2019je006195
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Sulfur‐Water Chemical System in the Middle Atmosphere of Venus

Abstract: Sulfur‐water chemistry plays an important role in the middle atmosphere of Venus. Ground‐based observations have found that simultaneously observed SO2 and H2O at ~64 km vary with time and are temporally anticorrelated. To understand these observations, we explore the sulfur‐water chemical system using a one‐dimensional chemistry‐diffusion model. We find that SO2 and H2O mixing ratios above the clouds are highly dependent on mixing ratios of the two species at the middle cloud top (58 km). The behavior of sulf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Photochemical models have been developed to model the behavior of water vapor and sulfur dioxide at the cloud top and within the clouds of Venus (Parkinson et al 2015). Using a 1D chemistry-diffusion model (Zhang et al 2012), Shao et al (2020) have found that the anti-correlation of SO 2 and H 2 O at 64 km can be generally explained by the sulfur chemistry in the middle atmosphere (58-100 km) of Venus. Even when SO 2 and H 2 O vary randomly at the middle cloud top (58 km), their model finds that the two species at 64 km are mostly anti-correlated, because SO 2 and H 2 O modulate each other through the sulfuric acid formation and intermediate SO 3 reactions at 64 km.…”
Section: Comparative Evolution Of So 2 and H 2 Omentioning
confidence: 99%
“…Photochemical models have been developed to model the behavior of water vapor and sulfur dioxide at the cloud top and within the clouds of Venus (Parkinson et al 2015). Using a 1D chemistry-diffusion model (Zhang et al 2012), Shao et al (2020) have found that the anti-correlation of SO 2 and H 2 O at 64 km can be generally explained by the sulfur chemistry in the middle atmosphere (58-100 km) of Venus. Even when SO 2 and H 2 O vary randomly at the middle cloud top (58 km), their model finds that the two species at 64 km are mostly anti-correlated, because SO 2 and H 2 O modulate each other through the sulfuric acid formation and intermediate SO 3 reactions at 64 km.…”
Section: Comparative Evolution Of So 2 and H 2 Omentioning
confidence: 99%
“…The sulfur dioxide abundances at the cloud tops having a strong relationship to the convective mixing strength (as well as sulfur dioxide and water abundances at the cloud‐base) has been established in multiple chemical modeling studies (Bierson & Zhang, 2019; Krasnopolsky, 2012, 2018; Parkinson et al., 2015). The dependence of cloud top sulfur dioxide on water abundance is complex, with correlated and anticorrelated behavior manifesting depending on whether water or sulfur dioxide is the relatively more abundant species at the convective cloud top (Shao et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical modeling of Venus has thus far focused primarily on calculating steady state abundances, since models which fully couple chemistry and dynamics still do not exist for Venus (Marcq et al., 2018; Shao et al., 2020). Thus, in this section we start with results from such steady state chemical calculations and then couple the shifts between steady states and dynamical variability.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Incidentally, other interesting measurements could be obtained during the occultations of calibration stars through the Venusian mesosphere to derive constraints of the vertical profiles of gaseous and particulate species above the clouds. Also, glory observations would allow us to retrieve microphysical properties of cloud aerosols, so that the complex interactive process of photochemistry (Shao et al, 2020) and cloud aerosol formation (McGouldrick, 2017) could be analyzed comprehensively.…”
Section: Discussionmentioning
confidence: 99%